Women Born to Older Mothers Have Reduced Fertility. Evidence From a Natural Fertility Population - Niels van den Berg; Ingrid K. van Dijk; Rick J. Mourits (Historical Life Course Studies)
Are daughters of older mothers less fertile? The human mutation rate is high and increases with chronological age. As female oocytes age, they become less functional, reducing female chances at successful reproduction. Increased oocyte mutation loads at advanced age may be passed on to offspring, decreasing fertility among daughters born to older mothers. In this paper we study the effects of maternal ageing on her daughter's fertility, including total number of children, age at last birth, and neonatal mortality among her children. We study fertility histories of two generations of women from mutually exclusive families from a pre-demographic transition historical population in the Dutch province of Zeeland. Using mixed effect Poisson and linear models to take within family (sibling) relations into account, we show that among married daughters fertility is reduced for those who were born to mothers with an advanced maternal age, resulting in fewer children ever born and earlier ages at last birth. We do not find consistent evidence for effects on neonatal mortality. These results may indicate that women born to older mothers are negatively affected by their mothers' increased age.